2021
DOI: 10.3390/su13020873
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Industrial By-Products/Waste to Manufacture Geopolymer Cement/Concrete

Abstract: There has been a significant movement in the past decades to develop alternative sustainable building material such as geopolymer cement/concrete to control CO2 emission. Industrial waste contains pozzolanic minerals that fulfil requirements to develop the sustainable material such as alumino-silicate based geopolymer. For example, industrial waste such as red mud, fly ash, GBFS/GGBS (granulated blast furnace slag/ground granulated blast furnace slag), rice husk ash (RHA), and bagasse ash consist of minerals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…The total composition of silicon dioxide and aluminum oxide is 40.9%. The calcium oxide (CaO) content in GGBS will also increase the early strength of geopolymer produced [ 41 , 42 , 43 , 44 ]. GGBS and alkali activator solution reaction forms calcite (CaCO 3 ) and calcium silicate hydrate (C-S-H) within the geopolymer matrix [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The total composition of silicon dioxide and aluminum oxide is 40.9%. The calcium oxide (CaO) content in GGBS will also increase the early strength of geopolymer produced [ 41 , 42 , 43 , 44 ]. GGBS and alkali activator solution reaction forms calcite (CaCO 3 ) and calcium silicate hydrate (C-S-H) within the geopolymer matrix [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas [34] has reported a molarity of 20 as an upper limit for the activator. Furthermore, the cost effectiveness of alkali activator ingredients in terms of energy consumption has also been raised [35][36][37][38]. For example, it is reported that 39% and 49% energy consumption is associated with the production of NaOH and Na 2 SiO 3 respectively, and also contributes to the overall cost of the geopolymer.…”
Section: Activator Liquidmentioning
confidence: 99%
“…To maintain low-cost energy requirements for these activators, an alternative waste solution that is rich in aluminosilicates can be sourced. One option is the Bayer's solution as suggested in [38].…”
Section: Activator Liquidmentioning
confidence: 99%
“…As for the alkaline activated blast furnace slag (AAS), which, according to Davidovits [ 16 ] it is not a geopolymer, Głuchowski [ 17 ] had the greatest contribution. The development of knowledge about AAS and geopolymers continues [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The works on the issues of CO 2 reduction in construction is carried out intensively around the world and the manufactured products have various terms: “green concrete”, “green cement” and “eco-concrete” [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%